Effects of polystyrene nanoplastics on lead toxicity in dandelion seedlings. (1st August 2022) - Gao, Minling; Bai, Linsen; Li, Xitong; Wang, Shengli; Song, Zhengguo
Abstract: Increasing rates of commercialization and industrialization have led to the comprehensive evaluation of toxic effects of microplastics on crop plants. However, research on the impact of functionalized polystyrene nanoplastics on the toxicity of heavy metals remains limited. This study investigated the effects of polystyrene, carboxy-modified polystyrene, and amino-modified polystyrene on lead (Pb) toxicity in dandelion seedlings. The results showed that carboxy -modified polystyrene with a negative charge absorbed more Pb 2+ than polystyrene and amino-modified polystyrene, and their maximum adsorption amounts were 5.328, 0.247, and 0.153 μg g −1, respectively. The hydroponic experiment demonstrated that single amino-modified polystyrene was more toxic to dandelion seedlings than polystyrene and carboxy-modified polystyrene. The presence of Pb 2+ was found to increase antioxidant enzymes (superoxide dismutase and catalase) and non-antioxidant enzymes (glutathione and ascorbic acid) activities in response to excessive reactive oxygen species in dandelion leaves and roots treated with polystyrene and carboxy-modified polystyrene, while it did not change much when amino-modified polystyrene was added. Interestingly, compared with single Pb 2+, the addition of amino-modified polystyrene with positive charges induced an obvious decrease in the above parameters; however, they declined slightly in the treatments with polystyrene and carboxy-modified polystyrene despite a stronger adsorption capacity for Pb 2+ . Similarly, the bioactive compounds, including flavonoids, polyphenols, and polysaccharides in dandelion, showed a scavenging effect on O2 − and H2 O2, thereby inhibiting the accumulation and reducing medicinal properties. This study found that the effects of microplastics on the uptake, distribution, and toxicity of heavy metals depended on the nanoparticle surface charge. Graphical abstract: Image 1 Highlights: Pb raised an induction of polystyrene (PS) and carboxy-modified PS (PS–COOH) on enzyme. Single amino-modified PS had greater toxic effects on dandelion than PS and PS-COOH. The presence of Pb increased the inhibition of PS and PS-COOH on bioactive compound. Effects of PS on the toxicity of Pb depended on the nanoparticle surface charge.